Reflexão crítica sobre o trabalho com projetos na história de uma escola inovadora - Giovedi, Maria Antonieta (2016)
This research is about seeking a critical reflection, as proposed by Smyth (1992), and has the aim of analyzing and assessing, in a critical way, the historicity of a school and the way such historicity has marked the activities of the curricular organization project named REDE Project. Its theoretical reference was based on the theories about curriculum (ROLDÃO, 1994; SACRISTÁN, 2000; TORRES, 1994), work with projects (BOUTINET, 1999), the teaching staff formation (IMBERNÓN, 2000; NÓVOA, 2009; TARDIFF, 2005) and Creative Chain (LIBERALI, 2012). The methodology was based on the conception of Creative Chains (LIBERALI, 2012), which envisages the possibility of interventions in school practices as from a cultural- historical- social understanding considering the relationships among the subjects of the research and the reconstruction of school practices. For this research I have used teachers' and directors' reports, videos of collective meetings, written accounts and school documents. Alongside the reflective course I have attempted to describe the cultural-historical-social context of the concerned school and relate it to the researcher's trajectory, as she is a director and formative trainer of the school. I have also described the REDE Project with reference to its implantation and its formative actions with teachers' teams. Based on such descriptions, practices were analyzed and new formative actions were planned together with the school professorate. The analysis of the formative activities carried out throughout 2015 has pointed out in which way the critical collaboration occurred in the body of those formations and has allowed the development of a new proposal for the continuation of the work in the REDE Project